Multiple types of cutaneous malignant tumors: A case report - Xuejun Gao; Yutong Liu; Xia Cai (SAGE Open Medical Case Reports)
Cutaneous malignant tumors are common, prevalent malignancies with high and rising incidence rates. Less attention has been paid to cutaneous malignant tumors because of their wide range of sites, variety of clinical manifestations, and low impact on daily life. In this paper, we report a case of a 57-year-old male who developed multiple cutaneous malignant tumors over a period of 3 years. The patient’s multiple cutaneous lesions did not receive timely intervention when initially identified. Recognition of disease etiological factors and prompt therapeutic intervention upon disease onset are of critical clinical importance.